Applied conversation analysis for counselling and psychotherapy researchers. Issue 2 (22nd March 2019) - O'Reilly, Michelle; Lester, Jessica
Abstract: Applied Conversation Analysis (CA) is broadly accepted to be a qualitative methodological approach associated with the discursive turn. Although some argue for a distinct observational science paradigm, the current methodological dichotomy positions this work under the qualitative rubric. Applied CA focuses on the sequential design of social interaction, examining language and meaning within institutional settings. It emphasises informing practice and provides a useful form of evidence for therapists and counsellors, as the work is grounded in real‐world therapeutic practices. In therapy, language and talk are fundamental to the process and outcomes. Studying therapeutic social interaction through Applied CA can illuminate processes, improve practice, and utilise best practice to inform care. The focus of this article is our perspective on the value of Applied CA as a form of evidence in counselling and psychotherapy, and to encourage partnership working between academics and clinicians working in the field.